The role of auxin in cell differentiation in meristems - Truskina, Jekaterina (2019)
Auxin regulates plant growth and development through the transcription factors of the AUXIN RESPONSE FACTOR (ARF) gene family. Most notably in Arabidopsis thaliana ARF5, 6, 7, 8 and 19 activate expression of target genes in response to auxin. These five ARF activators control both variable and overlapping processes during plant development including regulation of growth at the root and the shoot apical meristems, lateral root and axillary shoot formation. Each of the five ARF activators shows unique tissue-specific expression patterns in the root and the shoot associated with their distinct functions. This tissue-specific expression is likely derived from the differences in the control of ARF activator transcription. In this study the upstream regulators of ARF5, 6, 7, 8 and 19 transcription were identified. This was achieved by utilizing a high-throughput yeast one-hybrid (Y1H) method. The transient protoplast assay revealed that each ARF activator is controlled by specific transcriptional regulators and that the majority of these regulators are repressors of ARF transcription in planta. Mutants of the regulatory transcription factors were utilized to additionally investigate the interactions in planta. These mutants display auxin-related developmental phenotypes in the root and the shoot including alternations in growth kinetics, emergence of lateral organs, responses to auxin and altered expression of ARF activators. Furthermore, this study additionally focuses on cross-talk between the auxin and cytokinin signaling pathways and its role in root and shoot development. One of the interactions identified in the Y1H screen is a repression of ARF7 by CRF10, a member of the Cytokinin Response Factors gene family. The importance of this interaction in maintaining architecture of the root apical meristem, in leaf senescence and in the phototropic response to blue light in hypocotyls is studied.